2011
DOI: 10.3747/co.v18i1.681
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Monthly Out-of-Pocket Costs for Patients with Breast Cancer as Compared with Other Common Cancers in Ontario, Canada

Abstract: KEY WORDSBreast cancer, out-of-pocket costs, self-administered questionnaire, health care funding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 11 publications
2
46
1
Order By: Relevance
“…Out-of-pocket payments and changes to employment were common among participants in this study. While research in cancer care has also identified out-of-pocket payments as an unanticipated consequence of illness for Canadian patients (Housser et al 2013;Longo and Bereza 2011), unlike cancer treatments which are often time-limited, the participants in our study anticipated these costs for the duration of their children's lives. There was also a gendered aspect of this finding, as the majority of participants were women (N = 15) and many reported either decreasing their employment to part-time or leaving the workforce entirely in order to care for their children during times when they were hospitalized or to attend numerous appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-pocket payments and changes to employment were common among participants in this study. While research in cancer care has also identified out-of-pocket payments as an unanticipated consequence of illness for Canadian patients (Housser et al 2013;Longo and Bereza 2011), unlike cancer treatments which are often time-limited, the participants in our study anticipated these costs for the duration of their children's lives. There was also a gendered aspect of this finding, as the majority of participants were women (N = 15) and many reported either decreasing their employment to part-time or leaving the workforce entirely in order to care for their children during times when they were hospitalized or to attend numerous appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that few patients who face conditions with potentially high out-of-pocket costs were aware of financial assistance programs. For example, surveys of cancer patients show that only a minority of patients were aware of financial assistance programs or believed the programs were well advertised (Longo & Bereza, 2011;Longo et al, 2006;Longo et al, 2007;Mellace, 2010). Patients may not be fully aware of the cost implications of their condition when they are initially diagnosed and may become more concerned about out-of-pocket costs as they incur an ever-growing amount of expenses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the time and inconvenience of travel, rural residents can incur substantial travel-related costs to access and receive needed care. Several studies have described the travel and lodging costs for various health services including cancer care (Cohn, Gooenough, Foreman, & Suneson, 2003;Howard et al, 2014;Lauzier et al, 2011;Lightfoot et al, 2005;Longo & Bereza, 2011;Longo, Deber, Fitch, Williams, & D'Souza, 2007;Longo, Fitch, Deber, & Williams, 2006;Martin-McDonald, Rogers-Clark, Hegney, McCarthy, & Pearce, 2003;Zucca, Boyes, Newling, Hall, & Girgis, 2011), primary healthcare (Wong & Regan, 2009), abortion services (Sethna & Doull, 2007), and prenatal and maternity services (Fry, Cartwright, Huang, & Davies, 2003;Kornelsen & Grzybowski, 2006) in Canada and Australia where residents may live considerable distances away from regional and tertiary care centres. Longo et al (2006) found out-of-pocket costs posed a "significant or unmanageable" financial burden for roughly one fifth (20.4%) of cancer patients surveyed in Ontario, and that the costs related to travel were greater than the costs of all other out-of-pocket costs combined (Longo et al, 2007).…”
mentioning
confidence: 99%
“…The average costs of breast cancer care to health care systems are similar in all provinces and territories in Canada; however, additional costs for cancer care have been reported in the province of Ontario. Women with breast cancer in the province of Ontario are subjected to higher monthly out of pocket costs for patients such as costs of home health care, vitamins, alternative medicines and family care that are not covered by the provincial health plan (13).…”
Section: Burden Of Breast Cancermentioning
confidence: 99%